Maximilian Voloshin’s japanese print collection in the context of european orientalism - KOLTSOVA, DARYA (Journal of Education Culture and Society, 2020)
The paper is concerned with Maksimilian Voloshin’s Japanese woodblock print collec-tion. It starts with a short historical sketch of Orientalism in Europe and Russia, illustrating various highlights and the evolution of the image of the East in the minds of Europeans, and designed so that the emergence of Voloshin’s interest in Japanese art and his activity of collecting Ukiyo-e prints can be considered in the context of European Orientalism.